KARAKTERISTIK CAMPURAN ASPAL PORUS DENGAN AGREGAT DARI LOLI DAN TAIPA - Hendrik, Hendrik; Setiawan, Arief; Mashuri, Mashuri (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
One type of pavement that was developed in the surface layer is porous asphalt. Characteristics of porous asphalt mixture is not only influenced by the percentage of the aggregate but also influenced by the characteristics of the aggregates. Sources of different materials will provide different material characteristics. The purpose of this study was to investigate the characteristics of porous asphalt mix material from several sources, namely Loli (Donggala) and Taipa (Palu) in the province of Central Sulawesi. The study was conducted to test the feasibility of testing the material then mix in accordance with the specifications that cantabro test, permeability, drain down and Marshall test. The results showed that based on the characteristics of porous asphalt aggregate mixture Taipa superior to other aggregate and aggregate third source can be used as porous asphalt mixture.